Outcomes of a pilot randomized clinical trial testing brief interventions to increase HIV pre-exposure prophylaxis uptake among rural people who inject drugs attending syringe services programs - Hilary L. Surratt; Sarah Brown; Abby L. Burton; Will Cranford; Laura C. Fanucchi; Christie Green; Stephanie M. Mersch; Rebecca Rains; Philip M. Westgate (Therapeutic Advances in Infectious Disease)
Background: Kentucky is one of seven states with high, sustained rural HIV transmission tied to injection drug use. Expanding access to pre-exposure prophylaxis (PrEP) has been endorsed as a key HIV prevention strategy; however, uptake among people who inject drugs (PWID) has been negligible in rural areas. Syringe services programs (SSPs) have been implemented throughout Kentucky’s Appalachian region, providing an important opportunity to integrate PrEP services. Objectives: The primary objective was to examine preliminary efficacy and effect sizes of the study interventions on PrEP initiation among HIV-negative PWID. Design: Parallel group randomized controlled trial. Methods: Eighty participants were enrolled from two rural SSP locations in southeastern Kentucky. Following informed consent, participants completed a baseline interview, and were randomized to the intervention comparators. The primary endpoint was PrEP initiation, measured by dispensed PrEP prescription, within the 6-month study period. Analyses employed intent-to-treat (ITT) and per protocol approaches. Results: In total, 77/80 enrollees (96.2%) completed at least one session of their assigned intervention, regardless of trial arm. Seventy (87.5%) were linked to the embedded PrEP provider for the initial clinical visit; 38 (47.5%) completed a follow-up clinical visit with the provider, 22 (27.5%) were issued a prescription, and 7 (8.8%) initiated PrEP during the study period. We observed a 12.1% difference (14.6% vs 2.5%; ITT) and 12.8% difference (15.4% vs 2.6%; per protocol) in the primary outcome (PrEP initiation), in favor of the experimental intervention. Conclusion: This pilot trial established proof of concept for integrated PrEP care within SSPs in rural areas, and demonstrated a clinically meaningful difference in PrEP initiation between interventions, which warrants examination in a larger trial. Rates of early care discontinuation indicate a need for ongoing patient engagement strategies and implementation support for community SSPs. Trial registration: Prospective registration with ClinicalTrials.gov, NCT05037513 (registered August 5, 2021).